2013
DOI: 10.1053/j.ajkd.2012.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Association of Intradialytic Blood Pressure Variability With Increased All-Cause and Cardiovascular Mortality in Patients Treated With Long-term Hemodialysis

Abstract: Background Blood pressure is known to fluctuate widely during hemodialysis; however, little is known about the association between intradialytic blood pressure variability and outcomes. Study Design Retrospective observational cohort Setting & Participants A random sample of 6,393 adult, thrice-weekly, in-center, maintenance hemodialysis patients dialyzing at 1,026 dialysis units within a single large dialysis organization. Predictor Intradialytic systolic blood pressure (SBP) variability. This was calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
107
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(114 citation statements)
references
References 33 publications
(39 reference statements)
3
107
0
4
Order By: Relevance
“…Strict BP control, however, is challenging in the ESRD population, and the relationship between IDH and predialysis and postdialysis BP is complex (9,14). One study examined strict control of BP to minimize the risk of hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strict BP control, however, is challenging in the ESRD population, and the relationship between IDH and predialysis and postdialysis BP is complex (9,14). One study examined strict control of BP to minimize the risk of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…We do know that IDH is related to interdialytic weight gain (IDWG), which has been associated with higher risk of all-cause mortality, CV events, and CV mortality (8,9). Greater IDWG implies the need for more rapid fluid removal because dialysis time is essentially fixed for individual patients.…”
Section: Introductionmentioning
confidence: 99%
“…9 Flythe et al examined BP fluctuations during dialysis (i.e., intradialytic BPV) and reported a link between intradialytic BPV and all-cause and cardiovascular death. 10 In a prior study, the same authors identified older age, shorter dialysis vintage, and greater ultrafiltration (rate and volume) as associated with greater intradialytic BPV. 11 Contrary to findings in the general population, neither Chang et al nor Flythe et al found antihypertensive agents to play a significant role in visit-to-visit or intradialytic BPV-outcome associations among HD patients.…”
mentioning
confidence: 97%
“…9 Patients are treated with 1 mg/kg agalsidase-b intravenously every other week or 0.2 mg/kg agalsidase-a every other week; other than the amount of infused protein, there appears to be very little difference between the two products. 10,11 There may be differences in the response to ERT, and it appears that the 5-fold difference in the delivered dose could affect the stabilization of renal function, at least in some patients. 12,13 The issue of effective ERT dosing for Fabry disease was brought into sharp focus by an unfortunate lapse in manufacturing practices that resulted in a worldwide shortage of the Genzyme product (Fabrazyme) between June 2009 and January 2012.…”
mentioning
confidence: 99%
“…Some studies demonstrated that visit-tovisit BP variability was a novel risk factor for stroke (3), cardiovascular events (3), and all-cause mortality in the general population (6). It is reported that visit-to-visit BP variability also predicted cardiovascular events and allcause mortality in patients with chronic kidney disease (7,8) and hemodialysis (5,(9)(10)(11)(12)(13)(14). Note, however, that different dialysis modalities should have different effects on BP due to the intermittent nature of hemodialysis and continuous nature of peritoneal dialysis (PD).…”
Section: Introductionmentioning
confidence: 99%